The serotonergic system dysfunction in diabetes mellitus - Cai, Yan; Li, Xiaolong; Zhou, Hongli; Zhou, Jiyin (Frontiers in Cellular Neuroscience, 2022)
Most peripheral serotonin (5-HT) is synthesized in enterochromaffin cells, and most circulating 5-HT is stored in platelets. As a monoamine, 5-HT has several functions in various non-neuronal and neuronal systems. In the central nervous system, it functions as a neurotransmitter to modulate feeding behavior and mood. Numerous clinical trials have focused on increasing 5-HT activation in the central nervous system, including those involving anti-obesity drugs currently in the market, although severe side effects on peripheral system can lead to the withdrawal of certain drugs. Recent studies have revealed that both the peripheral and central serotonergic systems play a vital role in diabetes and its complications. This review summarizes the roles of the serotonergic system in blood glucose regulation, diabetic macroangiopathy, diabetic peripheral neuropathy, and diabetic encephalopathy, indicating its potential clinical significance as a therapeutic target for the treatment of diabetes and its complications.